2018
DOI: 10.1186/s10194-018-0930-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of community pharmacy professionals’ knowledge and counseling skills achievement towards headache management: a cross-sectional and simulated-client based mixed study

Abstract: BackgroundHeadache is one of the most common disabling medical condition affecting over 40% of adults globally. Many patients with headache prefer to alleviate their symptom with a range of over-the-counter analgesics that are available in community medicine retail outlets (CMROs). However, data regarding how community pharmacists respond to headache presentation and their analgesic dispensing behaviors in Ethiopia is scarce. The present study aimed to assess the self-reported and actual practice of community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
4
18
0
1
Order By: Relevance
“…On the contrary, gathering of past medical and medication history and allergy history were relatively less in frequency, and this may potentially expose patients to adverse events associated with drug-drug and/or drug-disease interactions. Similarly, the trend observed in the types of counseling information provided by community pharmacists is also consistent with published studies conducted in similar settings ( Kroeger et al, 2001 , Schneider et al, 2009 , Netere et al, 2018 , Puspitasari et al, 2009 ). The observed inadequacy in the frequency of counseling information could potentially compromise patient safety and increase the risks of medication use-related harms ( Eickhoff et al, 2012 , Bosse et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, gathering of past medical and medication history and allergy history were relatively less in frequency, and this may potentially expose patients to adverse events associated with drug-drug and/or drug-disease interactions. Similarly, the trend observed in the types of counseling information provided by community pharmacists is also consistent with published studies conducted in similar settings ( Kroeger et al, 2001 , Schneider et al, 2009 , Netere et al, 2018 , Puspitasari et al, 2009 ). The observed inadequacy in the frequency of counseling information could potentially compromise patient safety and increase the risks of medication use-related harms ( Eickhoff et al, 2012 , Bosse et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“… 21 In an Ethiopian SPM study, although ibuprofen was most frequently dispensed with 45.0%, this was against the background that SPs reported when asked that they were already taking paracetamol without noticeable relief. 22 In a Brazilian SPM study, when asked, SPs reported not taking medicines previously but not getting enough sleep and eating poorly. It turned out that the medicines dispensed and their proportions - with dipyrone or dipyrone and associations being the most frequently dispensed with 70.8% - were again different.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex mechanism of interaction, however, implementation of the guideline‐recommended consultations in daily practice is challenging (Kaae et al, 2013). Studies continue to demonstrate a worldwide need to improve guideline adherence (Alte et al, 2007; Berger et al, 2005; Brata, Gudka, Schneider, & Clifford, 2015; Brata et al, 2013; Langer et al, 2016; Netere et al, 2018). Therefore, our study highlights the gap between customers' expectations of consultations and the actual current practice of consultations.…”
Section: Discussionmentioning
confidence: 99%